2014
DOI: 10.15283/ijsc.2014.7.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Growth Properties and Pluripotency Marker Expression of Spontaneously Formed Three-dimensional Aggregates of Human Adipose-derived Stem Cells

Abstract: Background and Objectives:Recent findings suggest that therapeutic potential of mesenchymal stem cells (MSCs) could be increased through aggregation into three-dimensional (3D) bodies, and different culture methods have been employed to obtain 3D spheroids of MSCs. In the current study we report accidentally encountered spontaneous formation of adipose-derived stem cell (ASC) bodies in standard ASC culture of a single donor.Methods and Results:Human ASCs from passages 1 to 3, cultured in a medium containing 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Cyclical aggregation-planar expansion is necessary because MSCs lose function during planar expansion but are functionally enhanced during aggregation culture. Yet aggregated cells proliferate slower than planer cells [40][41][42] . Additionally, improvements of cellular properties have been shown to last one passage beyond aggregation 42 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cyclical aggregation-planar expansion is necessary because MSCs lose function during planar expansion but are functionally enhanced during aggregation culture. Yet aggregated cells proliferate slower than planer cells [40][41][42] . Additionally, improvements of cellular properties have been shown to last one passage beyond aggregation 42 .…”
Section: Discussionmentioning
confidence: 97%
“…For example, Yang et al observed that passaging MSCs resulted in loss of cell shape and function as early as passage 5 33 . Previously, it has been shown that aggregation of ASCs results in the retention of stem cell morphology 41 . This study demonstrates that the cyclical aggregation likewise maintained the spindle morphology.…”
Section: Discussionmentioning
confidence: 99%
“…No Oct 4 expression was revealed in 2D or 3D cultures of adipose derived human MSCs. Nanog expression was considerably increased in spheroids compared to 2D cultures (Bogdanova Jatniece et al, 2014). The authors have noticed that simultaneous expression of all three tran scription factors is required for pluripotency status.…”
Section: Surface Marker Expression In Fetmsc and Fetmsc And Their Sphmentioning
confidence: 98%
“…The expres sion of undifferentiated ESC markers in MSCs proba bly explains their higher differentiation potential (Wu et al, 2013). Enhanced expression of these markers in spheroids compared to monolayer cultures suggests that they are primitive subpopulations with multipo tent potential (Bogdanova Jatniece et al, 2014;Guo et al, 2014).…”
Section: Surface Marker Expression In Fetmsc and Fetmsc And Their Sphmentioning
confidence: 99%
See 1 more Smart Citation